ANALISIS BIAYA PRODUKSI HOMEMADE COOKIES COOKIEKU - Na'illatulloh, Syahda; Zanah, Nita Miftakhul; Fitriana, Noor Laila (UNIVERSITAS DHARMAWANGSA, 2024)
This research aims to analyze the production costs of homemade CookieKu Cookies located on Jl. Garuda 53, Banaran, Boyolali, Central Java. The data used refers to production costs in 2024. The research results show that direct raw material costs are IDR. 189,000, direct labor costs Rp. 560,000, and factory overhead costs of Rp. 1,074,000. The total production cost of CookieKu Cookies, with all factors taken into consideration, reached Rp. 1,823,000. The accuracy of data obtained through interviews and direct observation provides a strong basis for a comprehensive evaluation of production costs. The implications of the results of this research can be used to optimize production strategies, identify potential savings areas, and improve overall operational efficiency. With a better understanding of production costs, owners can make more informed decisions in managing their business. In addition, this research also provides valuable insights for other stakeholders, such as investors and suppliers, in understanding the company's cost structure and operational performance.